Does the Cost of Capital Affect Environmental Performance? - Haninun Haninun; Lindrianasari Lindrianasari; Susi Sarumpaet; Agrianti Komalasari (Indonesian Journal of Sustainability Accounting and Management, 2019)
This study aims to test the influence of environmental performance in Indonesia associated with the cost of capital. This research is motivated by previous findings which stated that the environmental performance received a good response from investors as reflected in increased stock prices (Ba et al., 2013; Middleton, 2015). The development hypothesis of the research is based on the theory of stakeholder, legitimacy and the theory of signal and some previous research such as the studies that have been done (Guenster et al., 2011; Sarumpaet et al., 2017). This type of research is research explanatory, the determination of the sample using the method of purposive sampling with number of samples to qualify as many as 215 observation data derived from the annual financial reports of companies listed on the stock exchange in 2015 until 2017. The results of the statistical analysis show that there are significant negative not significant on the relationship of environmental performance with cost of capital, it can be explained that only a small fraction of investors understand the performance information of the environment, and make it as a basis for making the decision to invest.